Working Safely in the Trades as Women: A Qualitative Exploration and Call for Women-Supportive Interventions - Curtis, Hannah M.; Meischke, Hendrika W.; Simcox, Nancy J.; Laslett, Sarah; Monsey, Lily M.; Baker, Marissa; Seixas, Noah S. (Frontiers in Public Health, 2022)
Background: Construction work offers women economic advancement and self-fulfillment opportunities, but multiple barriers prevent their increased representation in the industry. This study used qualitative methods to identity key physical and psychosocial safety hazards affecting tradeswomen. Methods: Three focus groups were held in 2015 with 19 tradeswomen in Washington State. Groups discussed workplace hazards and solutions to make the trades safer for women. Discussions were recorded, transcribed, and two independent reviewers analyzed themes. Results: Participants identified myriad physical and psychosocial hazards including a dangerous work environment, inadequate personal protective equipment, gender discrimination, and fear of layoff for reporting concerns. Conclusion: Findings suggest that the industry’s work environment can be hostile and unsupportive for women, contributing to tradeswomen’s injury risk and psychological distress. Future research and interventions should focus on understanding the relationships between and mediating the negative impact of women’s physical and psychosocial workplace hazards.